Characterization of Triacylglycerol Estolide Isomers Using High-Resolution Tandem Mass Spectrometry with Nanoelectrospray Ionization - Cudlman, Lukáš; Machara, Aleš; Vrkoslav, Vladimír; Polášek, Miroslav; Bosáková, Zuzana; Blanksby, Stephen J; Cvačka, Josef (Biomolecules, 2023)
Triacylglycerol estolides (TG-EST) are biologically active lipids extensively studied for their anti-inflammatory and anti-diabetic properties. In this work, eight standards of TG-EST were synthesized and systematically investigated by nanoelectrospray tandem mass spectrometry. Mass spectra of synthetic TG-EST were studied with the purpose of enabling the unambiguous identification of these lipids in biological samples. TG-EST glycerol sn-regioisomers and isomers with the fatty acid ester of hydroxy fatty acid (FAHFA) subunit branched in the ω-, α-, or 10-position were used. Ammonium, lithium, and sodium adducts of TG-EST formed by nanoelectrospray ionization were subjected to collision-induced dissociation (CID) and higher-energy collisional dissociation (HCD). Product ion spectra allowed for identification of fatty acid (FA) and FAHFA subunits originally linked to the glycerol backbone and distinguished the α-branching site of the FAHFA from other estolide-branching isomers. The ω- and 10-branching sites were determined by combining CID with ozone-induced dissociation (OzID). Lithium adducts provided the most informative product ions, enabling characterization of FA, hydroxy fatty acid (HFA), and FAHFA subunits. Glycerol sn-regioisomers were distinguished based on the relative abundance of product ions and unambiguously identified using CID/OzID of lithium and sodium adducts.
Keywords: Ozone; estolide-branching isomers; tandemová hmotnostní spektrometrie; lithium; high-resolution mass spectrometry; Tandem Mass Spectrometry; ionty; higher-energy collisional dissociation; Triglycerides; Sodium; mastné kyseliny; sodík; collision-induced dissociation; glycerol sn-regioisomers; glycerol; Glycerol; ozon; Ions; Fatty Acids; triglyceridy; triacylglycerol estolides; Lithium; ozone-induced dissociation